Quantitative analysis of the diffusion characteristics of China's long-term care insurance policy based on the PMC index model - Peixin Duan; Jiayi Wang; Ruisi Zhang; Haiyan Jia; Hui Sun; Yanfang Li (Frontiers in Public Health)
BackgroundPolicy pilots and policy diffusion are important tools for national governance and policy innovation in China. Long-term care insurance (LTCI) offers a potential solution to the challenges posed by the aging population. Currently, the pilot program for the LTCI system in China has gone through two phases, but a unified national policy framework has yet to be established. Therefore, the outcomes of the policy pilots and the diffusion process of this policy warrant further exploration.MethodBased on the perspective of policy diffusion, this study employs textual analysis and applies the Policy Modeling Consistency (PMC) index model to evaluate the quality and consistency of LTCI policies. A quantitative evaluation is conducted on 29 LTCI policies from two groups of pilot cities in China. The characteristics of policy diffusion are analyzed from both temporal and spatial dimensions.Conclusion(1) According to the PMC index results, LTCI policies of 25 cities achieved an excellent level, 4 cities reached an acceptable level, and there were no substandard policies among the 29 pilot cities. The overall consistency of LTCI policies in the first batch of pilot cities in China is higher than that in the second batch, with PMC index of 6.61 and 6.23. The LTCI policy still faces many challenges, such as limited funding sources and a narrow scope of care services. (2) The diffusion of LTCI policy across different regions and batches has the following characteristics: the diffusion of LTCI policy has followed an “M-shaped” curve over time. In terms of spatial diffusion, there is an interaction between spatial proximity and social proximity effects. In terms of diffusion pathways, there is a combined effect of vertical and horizontal diffusion, reflecting a hierarchical diffusion pattern.DiscussionThis paper constructs a new analytical framework for studying policy diffusion. Based on the analysis of policy texts using the PMC model, we focus on the analysis of policy quality and consistency to the diffusion characteristics and exploring the underlying reasons for the diffusion of the LTCI policies. This extends the research of LTCI policy from traditional qualitative analysis to the quantitative research domain.